The globalization of the health-care industry : opportunities for the Caribbean - Bernal, Richard L. (2007)
Discusses the globalization of the health-care industry and points out the opportunities that this process has created for some developing countries. Suggests that the provisions of healthcare has significant potential for those developing countries that can provide world-class services and facilities at internationally competitive prices. Indicates that the proximity of the Caribbean to the United States gives it an additional advantage in meeting the rapidly growing demand for health care originating in that country.